Fintech Based Peer-too-peer (P2P) Lending : A Perspective of MSMEs In the New Normal Era of Pandemic Covid-19 - Tuti Zakiyah (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2021)
The purpose of this research is to find out the role of Fintech Peer to Peer (P2P) lending based on the perception in the new normal era of Covid-19 as a financial inclusion for the recovery of the MSME financial sector. The population of this research is MSMEs in Central Java and East Java Provinces. The survey method was carried out by collecting data using a questionnaire as a data collection tool. In addition, researchers also use purposive sampling method to determine the sample. The analysis hypothesis is used the outer model and EViews 10 for the evaluation of the inner model. The results of this study are that peer to peer  lending together has a significant effect on the interests of MSME actors in East Java in The New Normal Era of the Covid-19, this is also supported by the Adjevtive R value which shows the number 87%.